If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 130 + -3x = 24x + -16 Reorder the terms: 130 + -3x = -16 + 24x Solving 130 + -3x = -16 + 24x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24x' to each side of the equation. 130 + -3x + -24x = -16 + 24x + -24x Combine like terms: -3x + -24x = -27x 130 + -27x = -16 + 24x + -24x Combine like terms: 24x + -24x = 0 130 + -27x = -16 + 0 130 + -27x = -16 Add '-130' to each side of the equation. 130 + -130 + -27x = -16 + -130 Combine like terms: 130 + -130 = 0 0 + -27x = -16 + -130 -27x = -16 + -130 Combine like terms: -16 + -130 = -146 -27x = -146 Divide each side by '-27'. x = 5.407407407 Simplifying x = 5.407407407
| (8x+9)(3x^2+7x+7)= | | 3x+10=86-9x | | h=13gh | | c=b+bcd | | x^2-8x+16=2x+16 | | 6w^2+31w+40=0 | | 5(x-4)=4-3x | | x+2+3+3+3-3=51 | | 2ln(x+9)-8lnx= | | lne^3x= | | 9(2y-9)-(8y+5)= | | 13+18x=535 | | 12+20x=132 | | (5x+1)(4x^2+2x+3)= | | 3t=-2 | | 7x^4-63x^2=0 | | 8b-6a-5a+6b= | | 3x^3=12 | | 4r=4 | | 18x^2=6x^4 | | 9p+7p+6p= | | 2x+15x= | | 59-7x=20x+17 | | x=14-8 | | 6(r-3)-2(r+5)+10= | | 56-3x=10x+17 | | p-7=9 | | 92-2x=43x+17 | | 2x^3+x^2+13x+84=0 | | 2x-4=10x-64 | | 112r^3+34r^2-6r=0 | | -4x-7y=5 |